(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
In this study, a spatial model of a steel truss arch bridge was established using the finite element software Midas/Civil to simulate and analyze the jacking construction process. The stress performance of the guide beam and main structure at each jacking stage was obtained. The results showed that in the first stage of jacking, the maximum stress and deflection values of the main girder were observed. The maximum stress on the upper edge of the main girder was 34.9MPa, and on the lower edge, it was -60.4MPa. The maximum deflection was -35.88mm. The maximum stress in the guide beam occurred during the jacking process and was -53.2MPa, corresponding to the cross-section at the root of the guide beam. The maximum deflection of the guide beam occurred in the maximum cantilever state and was -30.79mm. During the arch rib jacking process, the maximum stress was -49.4MPa. Both the maximum stress and deflection values were within the allowable range, indicating that the structure was in a safe state. This study provides a reference for similar bridge jacking construction projects.